2017
DOI: 10.1155/2017/6290248
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Discrete-Time Optimal Controls for an Isolated Signalized Intersection

Abstract: A classical control problem for an isolated oversaturated intersection is revisited with a focus on the optimal control policy to minimize total delay. The difference and connection between existing continuous-time planning models and recently proposed discrete-time planning models are studied. A gradient descent algorithm is proposed to convert the optimal control plan of the continuous-time model to the plan of the discrete-time model in many cases. Analytic proof and numerical tests for the algorithm are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, through actual observation, it is found that due to the different channelization design of intersections and traffic conditions, the parameters such as saturated flow rate and loss time will change accordingly, which leads to the failure of optimization objective function and unreasonable timing scheme [9][10][11][12] . Therefore, this paper analyzes the characteristics of traffic flow release at high load intersection, puts forward the calculation model of traffic flow release rate and loss time, and further designs the signal timing optimization model of high load intersection, in order to provide guidance for signal timing design of oversaturated intersection [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…However, through actual observation, it is found that due to the different channelization design of intersections and traffic conditions, the parameters such as saturated flow rate and loss time will change accordingly, which leads to the failure of optimization objective function and unreasonable timing scheme [9][10][11][12] . Therefore, this paper analyzes the characteristics of traffic flow release at high load intersection, puts forward the calculation model of traffic flow release rate and loss time, and further designs the signal timing optimization model of high load intersection, in order to provide guidance for signal timing design of oversaturated intersection [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…In the traditional sense, the improvement of intersection efficiency mostly focuses on the optimization of intersection signal control. Tan et al [6] studied the continuous-time and discrete-time signal timing models for the classical isolated signalized intersection with only two one-way vehicle flows and proposed a gradient descent algorithm. Wu et al [7] established a cellular automata model with greedy algorithm for the traffic control of intersections in autonomous vehicle environment.…”
Section: Introductionmentioning
confidence: 99%